CUSTOMER LOYALTY IN QRIS-BASED MSMES: THE MEDIATING ROLE OF SATISFACTION - Ery Sulistyorini; Burhanuddin Jauhari; Irany widyastiti (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
The rapid growth of digital payment systems has accelerated the transition toward a cashless economy, particularly through QRIS adoption among micro, small, and medium-sized enterprises (MSMEs) in Indonesia. Despite its widespread implementation, limited studies have examined customer loyalty from a post-adoption perspective. This study aims to investigate the effects of perceived ease of use and perceived security on customer satisfaction and loyalty among QRIS users in MSMEs, with customer satisfaction serving as a mediating variable. A quantitative explanatory approach was employed using a cross-sectional survey of 120 QRIS users in Malang City, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that perceived security is the strongest determinant of both customer satisfaction and loyalty, while perceived ease of use significantly influences satisfaction but not loyalty. Customer satisfaction emerged as the most influential predictor of loyalty and mediated the relationships between technological perceptions and loyalty. This study extends the Technology Acceptance Model to post-adoption behavior and highlights the strategic role of security in digital payment ecosystems. However, the findings are limited to a single-city context. Future studies should employ larger and multi-regional samples to improve generalizability.